2012
DOI: 10.1016/j.ijgo.2012.01.022
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization at a public hospital in Nigeria

Abstract: Successfully conducting an assisted reproduction program at a public health facility is feasible in a low-resource country. Treating couples in batches was cost effective, with a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
17
2
Order By: Relevance
“…The main findings of the current study were that the number of eggs retrieved, fertilized ovum, the number of embryos successfully transferred and the rate of successful induction of pregnancy depend on age of the woman and endometrial thickness. The pregnancy rate (20.9%) in this study was lower than the rates recently reported in Nigeria (30%; Orhue et al , 2012 ); Tunisia (32.4%; Fourati et al , 2009 ), Vienna, Austria (27.3%; Nouri et al , 2015 ) and in Singapore ( Tan et al , 2014 ). It is worth mentioning, however, that all of these studies (with exception of Fourati et al ) report the pregnancy rate following IVF/ICSI and not the rate following ICSI alone, as in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…The main findings of the current study were that the number of eggs retrieved, fertilized ovum, the number of embryos successfully transferred and the rate of successful induction of pregnancy depend on age of the woman and endometrial thickness. The pregnancy rate (20.9%) in this study was lower than the rates recently reported in Nigeria (30%; Orhue et al , 2012 ); Tunisia (32.4%; Fourati et al , 2009 ), Vienna, Austria (27.3%; Nouri et al , 2015 ) and in Singapore ( Tan et al , 2014 ). It is worth mentioning, however, that all of these studies (with exception of Fourati et al ) report the pregnancy rate following IVF/ICSI and not the rate following ICSI alone, as in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…Despite the fact that the first IVF centre in Nigeria was established in the eighties 10 the cost is still prohibitive. A single IVF treatment costs around US$2500 but the minimum wage is just US$52.60 a month, therefore the average person cannot afford this option 11 . However Orhue et al recommended that treating the patients in batches may lower the cost of IVF for the individual patient 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous reduction in 47.7% of multiples. Average of three embryos transferred.Orhue et al (2012)Case note review to determine outcomes of ART.CPR 30.0%, MPR 20.0% b . Up to three embryos/transfer.…”
Section: Resultsmentioning
confidence: 99%